Status gizi dan perkembangan anak usia 3-5 tahun di Kabupaten Bogor - Davidson, Sarah Melati; Khomsan, Ali; Riyadi, Hadi (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2020)
Background: Malnutrition in children under five causes a variety of developmental disorders. The nutritional need for children aged 3-5 age is very critical to reach optimum growth and development. Objectives: The purpose of this study is to analyse the association between nutritional status using WAZ, HAZ, WHZ index with gross motor, fine motor, passive communication, active communication, cognitive, self-help ability and social behavior development childred aged 3-5 years old. Methods: Data was obtained from a study entitled Improving Child Growth and Development through Nutrition and Psychosocial Intervention in Early Childhood Education (PAUD) Setting in Rural Areas and was fully funded by the Nestle Foundation (NF), Switzerland. The study design was cross-sectional, with 120 children aged 3-5 years old as subjects. Locations and subjects were selected purposively in Bogor District. Nutritional status was assesed by WAZ, HAZ, and WHZ index. Child development was assessed by using Bina Keluarga Balita questionnaire.Results: Most of the subjects had good nutritional status dan development level. WAZ indicator significantly associated with gross motor dan cognitive development (p<0.05). HAZ indicator significantly associated with gross motor, active communication skills and cognitive development (p<0.05). WHZ indicator significantly associated with fine motor and cognitive children (p<0.05). Conclusion: Nutritional status is associated with child development.